A Process to Recycling Glass Fibers from Glass-Manufacturing Waste - B. J. Jody (The Minerals, Metals and Materials Society, 2003)
This paper describes a one-step thennal-treatment process, developed at Argonne National Laboratory, to remove all organic contaminants from the glass-fiber waste that is generated during the glass-fonning process. The recovcred glass fibers can then be recycled into new glass fibers or new glass products without adversely impacting the operations of the glass industry or the quality of its products. Our process involves shredding the waste to a manageable size and then processing it at temperatures below its melting point to remove the polymeric-coating layer. The glass industry generates more than 60,000 tons of glass-manufacturing waste annually in the glass-forming process alone. Recycling of this waste stream can keep this non-biodegradable waste out of the landfills. In addition, use of recycled glass lowers energy costs, by an average of about $5 per ton as compared to using virgin raw materials to make virgin glass fibers. This process will also reduce the emission of C02 by 17,400 tons a year and it will also reduce the emission of nitrogen oxides. Economic analysis of our process shows a potential payback of less than 2 years.